Years of conflict : adolescence, political violence and displacement - Hart, Jason, 1963- (Studies in forced migration, 2010)
Recent years have witnessed a significant growth of interest in the consequences of political violence and displacement for the young. However, when speaking of "children" commentators have often taken the situation of those in early and middle childhood as representative of all young people under eighteen years of age. As a consequence, the specific situation of adolescents negotiating the processes of transition towards social adulthood amidst conditions of violence and displacement is commonly overlooked. Years of Conflict provides a much-needed corrective. Drawing upon perspectives from.